2013
DOI: 10.1371/journal.pone.0053059
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Vitamin D Status Prediction Model in Danish Pregnant Women: A Study of the Danish National Birth Cohort

Abstract: Vitamin D has been hypothesized to reduce risk of pregnancy complications such as preeclampsia, gestational diabetes mellitus, and preterm delivery. However, many of these outcomes are rare and require a large sample size to study, representing a challenge for cohorts with a limited number of preserved samples. The aims of this study were to (1) identify predictors of serum 25-hydroxy-vitamin D (25(OH)D) among pregnant women in a subsample (N = 1494) of the Danish National Birth Cohort (DNBC) and (2) develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
27
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 37 publications
14
27
4
Order By: Relevance
“…Vitamin D deficiency among women born in Africa was also less common (50%) than previously indicated (90% among Swedish women born in Somalia) [15]. Risk factors for vitamin D deficiency (25(OH)D <30 nmol/L) in early pregnancy were in line with previous findings [13,17,27]. The determinants in the subgroup born in Africa and Asia were fewer, indicating less effect of season but could possibly also be explained by lower power due to a smaller group size.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Vitamin D deficiency among women born in Africa was also less common (50%) than previously indicated (90% among Swedish women born in Somalia) [15]. Risk factors for vitamin D deficiency (25(OH)D <30 nmol/L) in early pregnancy were in line with previous findings [13,17,27]. The determinants in the subgroup born in Africa and Asia were fewer, indicating less effect of season but could possibly also be explained by lower power due to a smaller group size.…”
Section: Discussionsupporting
confidence: 83%
“…These studies were of small sample size and not representative of the general pregnant population. Danish studies have found average concentrations between 57 and 76 nmol/L and that between 3% and 10% of pregnant women have 25(OH)D levels <25 nmol/L [16,17,18]. Findings from England indicate a mean 25(OH)D of 62 nmol/L [19], while Scottish data indicate a lower mean, 40 nmol/L [20].…”
Section: Introductionmentioning
confidence: 99%
“…The winter finding is likely the result of chance. UV monitoring may have provided more accurate measurements of sun-exposure duration, however our research also corroborates a need for more sensitive sun-exposure questionnaires, which may be less expensively administered in epidemiologic studies but which have as yet rarely succeeded in capturing more than 40% of variation in vitamin D status in other populations [25]. …”
Section: Discussionsupporting
confidence: 66%
“…In other observational studies, clinical trials examining women later in gestation, and the current study's examination of neonatal cord blood, significant differences over twice this magnitude have been found between supplement users and non-users. 3,7,8,17 In a recent clinical trial, a mean increase of 10.5 nmol/L from baseline (mean 14 weeks' gestation) to delivery was observed in pregnant women assigned to 400 IU/day. 21 Nevertheless, a substantial proportion of supplement users still have low vitamin D status.…”
Section: Resultsmentioning
confidence: 99%
“…4 Given the evidence suggesting a beneficial effect of vitamin D in pregnancy and fetal dependence on maternal 25(OH)D, it is important to determine which of these factors help to identify pregnant women at risk of low vitamin D status and to estimate the effect they could have on 25(OH)D levels to inform the nature of potential interventions. However, few large studies have been conducted, [6][7][8][9][10][11] and none were in Canada. Therefore, our objective in this study of over 1,500 pregnant Canadian women was to determine the association between maternal characteristics and vitamin D status.…”
mentioning
confidence: 99%